DEFINITION OF DOMESTIC VIOLENCE: CONTENT AND INTERPRETATION - Kaļiņina, Jeļena (Administrative and Criminal Justice, 2017)
Domestic violence continues to be a global problem that kills and maims – physically, psychologically, sexually and economically. This problem is present in every country, cutting across boundaries of culture, class, education, income, ethnicity and age. Domestic Violence occurs in all kinds of intimate relationships, including married couples, people who are dating, couples who live together, parents, same-sex partners, people who were formerly in a relationship and teen dating relationships. It is enshrined in the Civil Procedure Law of the Republic of Latvia, but there is no specific definition of domestic violence. The vast majority of victims of violence are women and children. Domestic violence goes by many names, for example, wife abuse, woman battery, intimate violence, battering, partner abuse. Following sections of the Criminal Law of the Republic of Latvia are related to violence in general, not to domestic violence. There are no definitions of domestic/family violence in Latvian legislation. The purpose of this article: to identify problems which are connected with definition of the concept "domestic violence", determination of his content and interpretation.